From Madrid to Lima. Identity narratives of women returning to their community environments of origin - Ballesteros Molina, Cristy Lourdes (2023)
Objective: This investigative study contributes to analyze the identity construction of migrants of peruvian nationality who return to their community environments of origin, based on their narratives constructed and interpreted within the framework of their experiences during the process of return and reinsertion to their also transformed spaces and contexts that will structure their new agencies, subjectivities in a significant and representative way between the macro and the micro, the public and the private. Methodology: A qualitative methodological analysis of life stories was used to facilitate access to their daily experiences that take place between Madrid as a host community, and Lima as a reintegration community. Results: The results show that the return and reintegration are processes conditioned by structural logics, which interfere in the protagonist configuration of the identities of the migrants, being these more open, dialogic and flexible. Conclusions: It is concluded that the return of migrants and their reintegration into their original environments contribute to the configuration of new identities.